JOB PERFORMANCE KARYAWAN DISEKTOR PERBANKAAN DIPENGARUHI OLEH EMOTIONAL INTELLIGENCE DAN JOB SATISFACTION - Leonar Lexis; Dita Oki Berliyanti; Wiwik Robiatul Adawiyah (Business, Economics dan Entrepreneurship, 2023)
This study uses 3 variables consisting of: 1 Independent variable, namely Job Performance, 1 Mediation variable, namely Job Satisfaction and 1 Dependent variable, namely Emotional Intelligence which aims to analyze the influence of Emotional Intelligence on Job Performance mediated by Job Satisfaction. The sample used in this study were employees of the Bank BNI in Jakarta Barat. The sample was taken using a multi-stage stratified random sampling method, through a survey using a questionnaire with a total of 130 respondents and the data analysis method in this study using Structural Equation Models (SEM). with AMOS software version 23. through a survey using a questionnaire with the results of this study showing that Emotional Intelligence has a positive effect on Job Satisfaction. However, it has no significant effect on Job Performance. If you look at the role of Job Satisfaction as a Mediation variable, it is enough to give Emotional Intelligence an influence on Job Performance for the employees of Bank BNI Jakarta Barat. Thus, the conclusions obtained indicate that employees with high job satisfaction tend to perform well in their jobs compared to employees with low job satisfaction. In addition, the work performance of employees with high emotional intelligence is greater than the performance of employees with low emotional intelligence. Apart from the direct effect, this study shows that job satisfaction has a significant mediating role on the relationship between emotional intelligence and performance. These findings reveal important theoretical clues that emotional intelligence as a personal capability can affect job performance not only directly but also indirectly through its positive influence on job satisfaction.